The role of Coenzyme Q10 in statin-associated myopathy - Sanjay Kalra (Electronic Physician, 2009)
Statins, or 3-hydroxyl-3-methylglutaryl coenzyme HMG-CoA reductase inhibitors, are cholesterol-lowering drugs which are frequently used in the primary and secondary prevention of coronary artery disease. Current research and recommendations support and encourage more extensive use of these drugs.However, statin usage is limited by many factors, including a high incidence of statin-associated myalgia and myopathy. This review focuses on the use of Coenzyme Q in statin-associated myopathy.